2007
DOI: 10.1088/1751-8113/40/21/020
|View full text |Cite
|
Sign up to set email alerts
|

Eigenfunctional representation of dyadic Green's functions in multilayered gyrotropic chiral media

Abstract: Studying electromagnetic waves in complex media has been an important research topic due to its useful applications and scientific significance of its physical performance. Dyadic Green's functions (DGFs), as a mathematical kernel or a dielectric medium response, have long been a valuable tool in solving both source-free and source-incorporated electromagnetic boundary value problems for electromagnetic scattering, radiation and propagation phenomena. A complete eigenfunctional expansion of the dyadic Green's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Green's functions, including dyadic Green's functions (DGF) and scalar Green's functions (SGF), are powerful tools in electromagnetic theory [2][3][4], because the relationship between the field and excitation sources can be easily described by them. As a result, many years of effort have been devoted to obtaining Green's functions for inhomogeneous media [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] There are many approximation and numerical methods that have been utilized for calculating the DGF and SGF, such as the finite sum superposition method [3], the total least squares method [4], the fast full-mode method [5], the numerical modified steepest descent path method [5] and the numerically stable analysis method [6]. In addition, the pure theoretical derivations of Green's functions for the stratified media, without numerical approximation and error, were also pursued for a long time [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Green's functions, including dyadic Green's functions (DGF) and scalar Green's functions (SGF), are powerful tools in electromagnetic theory [2][3][4], because the relationship between the field and excitation sources can be easily described by them. As a result, many years of effort have been devoted to obtaining Green's functions for inhomogeneous media [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] There are many approximation and numerical methods that have been utilized for calculating the DGF and SGF, such as the finite sum superposition method [3], the total least squares method [4], the fast full-mode method [5], the numerical modified steepest descent path method [5] and the numerically stable analysis method [6]. In addition, the pure theoretical derivations of Green's functions for the stratified media, without numerical approximation and error, were also pursued for a long time [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many years of effort have been devoted to obtaining Green's functions for inhomogeneous media [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] There are many approximation and numerical methods that have been utilized for calculating the DGF and SGF, such as the finite sum superposition method [3], the total least squares method [4], the fast full-mode method [5], the numerical modified steepest descent path method [5] and the numerically stable analysis method [6]. In addition, the pure theoretical derivations of Green's functions for the stratified media, without numerical approximation and error, were also pursued for a long time [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The form of the dyadic Green's function has been presented based on the methods of generation function expansions [7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized materials can be designed to have their permittivity and permeability artificially of negative or positive values. Studies relevant to these materials focused on isotropic chiral media have been carried out by several authors [5][6][7][8][9][10][11][12]. However, from researches in chiral and in uniaxial chiral materials, it has been found that materials with complex properties can find more possible applications in the microwave and optical regions [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a chiral slab with negative refractive index has been shown to act as a perfect lens having subwavelength for circularly polarized waves [2,3]. Many other applications of the chiral metamaterials include but not limited to waveguides, antennas, polarization rotators, and cloaking surfaces [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%